Proceedings of the 21st ACM International Conference on Information and Knowledge Management 2012
DOI: 10.1145/2396761.2398674
|View full text |Cite
|
Sign up to set email alerts
|

Temporal models for microblogs

Abstract: Time information impacts relevance in retrieval for the queries that are sensitive to trends and events. Microblog services particularly focused on recent news and events so dealing with the temporal aspects of microblogs is essential for providing effective retrieval. Recent work on time-based retrieval has shown that selecting the relevant time period for query expansion is promising. In this paper, we suggest a method for selecting the time period for query expansion based on a user behavior (i.e., retweets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Previous works have also shown that time-based language modeling and relevance feedback approaches are effective for microblog search [4,8,9,19,22]. As described herein, we build on these findings and propose a novel PRF method combining lexical and document-dependent temporal evidence of microblog in response to a query, which relies strongly on relevance information among the re-retrieved documents, such as a word distribution and a time-stamp distribution.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous works have also shown that time-based language modeling and relevance feedback approaches are effective for microblog search [4,8,9,19,22]. As described herein, we build on these findings and propose a novel PRF method combining lexical and document-dependent temporal evidence of microblog in response to a query, which relies strongly on relevance information among the re-retrieved documents, such as a word distribution and a time-stamp distribution.…”
Section: Introductionmentioning
confidence: 73%
“…Query expansion based on relevance feedback has been shown effective for improving microblog search performance [4,19,22,23,26]. That is due to the fact that query expansion can overcome the severe vocabulary mismatch problem of microblog search.…”
Section: Introductionmentioning
confidence: 99%
“…Event-Related Image Search: Timestamped Query an often applied approach is so-called Pseudo Relevance Feedback [188,102,142]. The use of temporal information in Information Retrieval (IR), has been previously widely investigated both for ranking models [88] and query expansion [33]. Approaches incorporating geographical context in query expansion has, on the other hand, been mainly proposed in the field of Geographical Information Retrieval (GIR) systems [21,49,121,128].…”
Section: Relation To Other Workmentioning
confidence: 99%
“…In recent years, exploiting the temporal to boost the performance of microblog retrieval has become one of the hot issues in the field of microblog search [14][15][16][17][18]. A typical practice in existing studies is to re-estimate the term weight or document prior probability by introducing a temporal prior.…”
Section: Introductionmentioning
confidence: 99%